Analysis of Relationship between Chemical Oceanography Conditions and Coral Reef Ecosystems in Damas Waters, Trenggalek, East Java - Valessa Senshi Moira; Oktiyas Muzaky LuthfI; Andik Isdianto (Universitas Airlangga, 2020)
Indonesia is known as one of the world's marine biodiversity centers with its rich coral reefs. Coral growth depends on environmental conditions, which in reality do not always remain due to disruptions originating from nature or human activities. The growth of coral reefs in a sea water is strongly influenced by the quality of its waters such as chemical oceanographic factors namely salinity, pH, DO, nitrate and phosphate. The data collection was carried out twice in September and November 2019 in Damas Waters, Trenggalek, East Java. The waters of Damas Beach are located in Karanggandu Village, Watulimo District. The purpose of this study was to determine the condition of coral reefs in Damas Waters, to determine the effect of water quality on artificial reefs in chemistry in Damas Waters and to determine the relationship of quality parameters of chemical waters with artificial coral reefs in Damas Waters, Trenggalek, East Java. The sampling method is done by purposive random sampling that is determining the sample with certain considerations. The location points used by 20 stations are spread, namely on artificial reefs, natural coral reefs, open seas and the area around the harbor. Measurements made include in situ water quality with a multiparameter measurement tool, namely AAQ. The results obtained that in all stations found good water conditions for the life of coral reefs, and also the analysis of the relationship of each parameter and coral reefs influence each other.